Relation between Mean Velocity Index, Time Constant and Critical Closing Pressure in Patients with Subarachnoid Hemorrhage - Papaioannou, Vasilios; Budohoski, Karol; Placek, Michal; Czosnyka, Zofia; Smielewski, Peter; Czosnyka, Marek (Archives of Clinical and Biomedical Research, 2022)
Background: In patients suffering from Subarachnoid Hemorrhage (SAH), Delayed Cerebral Ischemia (DCI) is partly associated with Vasospasm (VS) and impaired cerebral autoregulation. We investigated the pattern of changes of different Transcranial Doppler (TCD)-derived indices of cerebrovascular dynamics during VS, in patients dichotomized by the presence of DCI. Methods: A retrospective analysis was performed using recordings from 32 SAH patients, diagnosed with VS through bilateral TCD measurements. Patients were divided in 2 groups, depending on development of DCI. Cerebral autoregulation was estimated using the moving correlation coefficient Mxa, calculated from spontaneous fluctuations of Cerebral Blood Flow Velocity (CBFV) and Arterial Blood Pressure (ABP). We also measured cerebral arterial time constant (tau) as the product of resistance (Ra) and Compliance (Ca) and Critical Closing Pressure (CrCP), using two different methods of assessment (CrCPAaslid and CrCPVarsos). Results: In the whole population (N=32), VS caused shortening of tau (ipsilateral to spasm: 0.17 ± 0.08 vs before: 0.25 ± 0.17 sec, p = 0.04), decrease in CrCPAaslid (ipsilateral to spasm: 9.69 ± 23.28 vs before: 27.23 ± 23.31 mmHg, p = 0.01) and interhemispheric asymmetry with lower values on ipsilateral side (p < 0.01). Ipsilateral CrCPAaslid during VS was negatively correlated with Mxa (r =-0.43, p=0.01), whereas CrCPVarsos exhibited positive correlation with tau (r=0.74, p < 0.001). In patients with DCI (N=19), VS caused increase in Mxa (ipsilateral to spasm: 0.36 ± 0.18 vs before: 0.26 ± 0.23, p = 0.04), decrease in CrCPAaslid (ipsilateral to spasm: 6.61 ± 24.5 vs before: 17.24 ± 19.4 mmHg, p = 0.04) and lower values on ipsilateral side (p < 0.01). Conclusions: During VS, tau and CrCP were reduced in